A new double flash process and heat integration for better energy utilization of toluene disproportionation. (September 2015) - Liu, K.; Zhang, B.J.; Zhang, Z.L.; Chen, Q.L.
Abstract: When a chemical complex has similar demands for both benzene and xylenes, toluene disproportionation is an attractive process to produce both benzene and p-xylene. Nevertheless, the conventional production process is heavily energy intensive with low economic benefits. In the conventional process, the high temperature reaction effluent of 458 °C is cooled to 36 °C for hydrogen separation. The flash liquid is then heated again and enters the stripper. The repeated effluent cooling and heating results in a low efficiency of energy utilization. A new double flash toluene disproportionation process for better energy utilization is presented in this study to avoid the repeated cooling and heating of the reaction effluent. The new and conventional processes are carefully compared on the basis of heat integration and economic evaluation. The new process reduces the hot utility by 13.27%, and the cold utility by 12.30%. Additionally, the investment in a heat exchanger network is decreased, while the income from products is increased. Highlights: We analyse heat flow of the conventional toluene disproportionation process. We present a new double flash toluene disproportionation process. We compare heat integration of the new and conventional processes. The new process decreases the hot utility by 13.27%, and the cold utility by 12.30%. The new toluene disproportionation process saves 16.68% of TAC.